Eating disorders in Spanish female athletes - Toro, J.; Galilea, B.; Martinez-Mallen, E.; Salamero, M.; Capdevila, L.; Mari, J.; Mayolas, J.; Toro, E. (International Journal of Sports Medicine, 2005)
The objective of the study was to determine the prevalence of eating disorders and risk factors for their development in female athletes. Two hundred and eighty-three elite sportswomen, competing in 20 different sports, were administered the EAT, the CETCA (the Eating Disorders Assessment Questionnaire, based on DSM-III-R diagnostic criteria), and two other inventories which evaluated 1) the possible influence on eating disorders of exposure of the body in public and 2) pressure from coaches regarding eating habits, weight, physical appearance and performance. More than 11 % of subjects had scores above the cut-off point (> 30) on the EAT questionnaire, a proportion similar to that found in a general female population in Spain. On the basis of the CETCA score, AN was putatively diagnosed in 2.5 % of the sample, and BN in 20.1 %. Though some of these cases may have been EDNOS (eating disorders not otherwise specified), the proportion of athletes suffering from some kind of eating disorder was five times higher than in the general population (22.6 % vs. 4.1 %). No differences were found between the sportswomen and the general population in terms of specific risk behaviours and attitudes, but a substantial subgroup of athletes presented two or more of these risk behaviours. Exposure of the body in public seems to be a risk factor for eating disorders in general, and pressure from coaches seems to be a risk factor for bulimia.